A comprehensive review of phytochemical profile, bioactives for pharmaceuticals, and pharmacological attributes of Azadirachta indica. (19th April 2018) - Saleem, Sumaira; Muhammad, Gulzar; Hussain, Muhammad Ajaz; Bukhari, Syed Nasir Abbas
Abstract : Azadirachta indica L. is a multipurpose medicinal tree of family Meliaceae . It occurs in tropical and semitropical regions of the world. Different parts of this miraculous tree are used to treat pyrexia, headache, ulcer, respiratory disorders, cancer, diabetes, leprosy, malaria, dengue, chicken pox, and dermal complications. The tree is popular for its pharmacological attributes such as hypolipidemic, antifertility, microbicidal, antidiabetic, anti‐inflammatory, hepatoprotective, antipyretic, hypoglycemic, insecticidal, nematicidal, antiulcer, antioxidant, neuroprotective, cardioprotective, and antileishmaniasis properties. A .  indica is also rich in various phytochemicals for pharmaceuticals such as alkaloids, steroids, flavonoids, terpenoids, fatty acids, and carbohydrates. The fungicidal potential of the tree is due to the presence of azadirachtin and nimbin. Herein, we have compiled a comprehensive review of phytochemical profile, pharmacological attributes, and therapeutic prospective of this multipurpose tree.